Bahasa Inggris - Salma Maulida Husana; Danial Danial; Afandi Sitamala (Dialogia Iuridica, 2026)
United Nations peacekeeping operations face legal ambiguities due to the expansion of robust mandates that blur the status of peacekeepers as non-combatants, creating gaps in protection and accountability in conflict areas such as the Democratic Republic of Congo (DRC). This study aims to analyze the legal regime governing the status and protection of Indonesian peacekeepers, examine the internalization of International Humanitarian Law (IHL) norms in national policy and training, and formulate recommendations for reform. This research employs a normative juridical method using statute, conceptual, and case approaches, with data collected through a systematic review of secondary legal materials, including international conventions, United Nations documents, and recent academic literature. The Democratic Republic of Congo (DRC) is selected as a representative case of complex United Nations peacekeeping mandates. The findings show that the liminal status of peacekeepers creates accountability gaps, particularly during Direct Participation in Hostilities (DPH) and Protection of Civilians (PoC) mandates. Furthermore, the internalization of International Humanitarian Law (IHL) within Indonesia’s Vision 4,000 Peacekeepers Roadmap remains fragmented, especially in aligning legal frameworks, training, and Rules of Engagement (ROE). This study recommends developing contextualized ROE, integrating DPH standards into training, and strengthening coordination between Indonesia and the United Nations. It highlights the need for clearer legal frameworks and stronger accountability mechanisms while providing insights for troop-contributing countries in enhancing the protection and responsibility of peacekeepers.